(untitled) (SYNAPSES: INSIGHTS ACROSS THE DISCIPLINES, 2024)
The insurance industry faces persistent challenges, including inefficiencies, fraud, and a lack of transparency, which result in high costs and customer dissatisfaction. Blockchain technology offers a transformative solution to these issues by providing a decentralized, immutable, and transparent ledger system. Through applications such as fraud detection, automated claims processing, and streamlined policy management, blockchain enhances operational efficiency and builds trust among stakeholders. This article explores the potential of blockchain in revolutionizing the insurance sector, highlights real-world examples, addresses challenges to adoption, and outlines a promising future outlook for the industry